Pengaruh Stimulus Dingin terhadap Tekanan Darah: Studi Cold Pressor Test pada Mahasiswa Kedokteran Universitas Tarumanagara Angkatan 2022 - Merry Oktavia; Susy Olivia Lontoh (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The Cold Pressor Test (CPT) is a non-invasive method used to evaluate sympathetic nervous system reactivity to cold-induced stress. An exaggerated blood pressure response to CPT may indicate a predisposition to cardiovascular dysregulation.This study aimed to determine the effect of the Cold Pressor Test on blood pressure among medical students. A quasi-experimental design was employed, involving 74 medical students from the 2022 cohort at Tarumanagara University, who were divided into test and control groups. Systolic and diastolic blood pressures were measured before and after the intervention. Data were analyzed using the paired t-test or Wilcoxon signed-rank test, depending on data distribution. Results: The findings showed no statistically significant differences in systolic or diastolic blood pressure before and after the CPT in either group (p > 0.05). Conclusion: The Cold Pressor Test did not cause significant changes in blood pressure among the medical students studied